Wide-field study of the peculiar globular cluster system hosted by the field lenticular NGC 1172 - Ennis, Ana Inés (2020)
We present a wide-field study of the globular cluster system (GCS) of the field lenticular galaxy NGC 1172, based on observations from GMOS/Gemini (optical), FourStar/Magellan (NIR), and archival data from ACS/HST (optical). This analysis covers the full extension of the GCS, and results in a value of specific frequency (S_N=8.6 ± 1.5) peculiarly high for an intermediate-mass galaxy in a low-density environment such as this one. We find that the GCS appears to be bimodal, although the colour distribution is narrow and does not allow for an accurate separation of the subpopulations. However, the combination of optical and NIR filters allows us to obtain an estimation of the metallicity distribution based on the photometry, which supports bimodality. We conclude that the presence of a large fraction of metal-poor globular clusters (GCs) and the high specific frequency point to NGC 1172 having accreted a significant amount of GCs from low-mass satellites in the past.